2014
DOI: 10.1017/s1751731114001694
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a promotes porcine myoblast proliferation by downregulating myostatin expression

Abstract: MicroRNAs are endogenous~22nt RNAs that negatively regulate gene expression at the posttranscriptional level via binding to the 3′-untranslated region (3′UTR) of target mRNAs. The microRNA miR-27a was reported to depress the expression of myostatin, a critical inhibitor of skeletal myogenesis, by binding to its 3′UTR in mouse. In this study, we cloned the full-length 3′UTR of porcine myostatin by rapid amplification of 3′-cDNA ends (3′-RACE) and demonstrated that the 3′UTR of porcine myostatin is targeted by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Porcine skeletal muscle satellite cells were isolated from 3-day-old male Duroc × Yorkshire × Landrace (DLY) pigs as described previously39 with some modifications. Briefly, skeletal muscles were digested with 0.2% collagenase type II (Sigma) and then filtered successively through 200-mesh and 400-mesh cell sieves.…”
Section: Methodsmentioning
confidence: 99%
“…Porcine skeletal muscle satellite cells were isolated from 3-day-old male Duroc × Yorkshire × Landrace (DLY) pigs as described previously39 with some modifications. Briefly, skeletal muscles were digested with 0.2% collagenase type II (Sigma) and then filtered successively through 200-mesh and 400-mesh cell sieves.…”
Section: Methodsmentioning
confidence: 99%
“…Further analysis revealed that miR‐27a/b‐mediated inhibition of myostatin has a role in promoting satellite cell (SC) activation, increasing myoblast proliferation, and preventing muscle wasting . Similarly, Yang et al, () have also demonstrated that miR‐27a positively regulates porcine myoblast proliferation through inhibiting myostatin .…”
Section: Regulation Of Myostatinmentioning
confidence: 96%
“…In skeletal muscle, highly expressed miRNAs are called myomiRs, which include miR-1, miR-133a, miR-133b, miR-206, miR-208a, miR-208b, miR-486 and miR-499 [ 23 ]. Besides the myomiRs, there are also many miRNAs regulating satellite cell myogenesis, for example miR-31 [ 24 ]; miR-27a [ 25 , 26 ], miR128 [ 27 ], miR-221/miR-222 [ 28 ], miR-682 [ 29 ] and miR-181 [ 30 ]; miR-186 [ 31 ], miR-24 [ 32 ], miR-214 [ 33 , 34 ], miR-26a [ 35 ], miR-29b/c [ 36 ], miR-322/424 [ 37 ] and miR-503 [ 37 ] have been identified to regulate the quiescence, proliferation and differentiation stage of satellite cells respectively. Both Notch signaling and miRNA have been identified to play critical roles in regulating myogenesis, and four miRNAs, miR-1, miR-206, miR-146a and 146b, have been reported to regulate skeletal muscle myogenesis via Notch signaling [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%